Comercialização dos alimentos agroecológicos e orgânicos nos circuitos curtos em Aracaju/SE - Santos, Letícia Menezes (2022)
Over the last decades, it has been grown family farmers involved in raising new agri-food alternatives that takes in consideration not only environment but also traditional knowledge. Besides tillage increase, there is also observed varied alternative places for these food marketing. Such strategies reinforce agricultural production diversification, and so contribute to autonomy, sovereignty and food security of farmers. Noticing the current practice reality of traditional people, social movements that struggles for land and academic discussions of specialized professionals, agroecology, at a transdisciplinary perspective, can be defined as a contra hegemonic movement, beyond sustainable techniques for producing resources, including values that integrates man and nature. This paper aims to analyze the relevance and social context, culture and economy of the family farmers on short circuits marketing of agroecological and organic products in Aracaju/SE. The development of the research was stablished by bibliographical review in thesis, dissertations, books and scientific articles that address agroecological production and short circuits of marketing. In addition to bibliographical review, we proceed research in official documents databases. Concurrently to field research on agroecological fairs, municipal markets through participant observation, photographic registry, field journal and semi structured interview followed by systematization and collected data analyses. Considering this research results, we conclude that agroecology is increasing on countryside and city. The need of a sustainable agriculture leads man to search new strategies to promote sustainable tillage, “socially fair”, “economically possible” and “ecologically balanced". In that regard, agroecological and organic agriculture of the family farmers of Sergipe shows itself as a possible alternative to food growing based on knowledge end knowhow through different generations and contributes to building up new ways of socioenvironmental relation, made on cooperation, solidarity and life respect. Furthermore, in short circuits, it is noticed a demand of consumers for that kind of food on market places, social medias or digital market, the strengthen of countryside and city brotherhood, the visibility of families, associations, family farmers network and social movements and the relevance of agroecological and organic agriculture to social development of these family farmers.